P-183 Addressing inequality in palliative care provision in heart failure. Issue Volume 9: Issue (2019)Supplement 4 (17th November 2019) - Chumbley, Karen; Kasznicka, Beata; O'Neill, Sue; West, Wendy; Andrews, Ness
Abstract : Background: There is an urgent need to address the inequality in palliative care provision for people living with heart failure. North East Essex has a changing demographic, with a predicted 25% increase in the population over 76 years old (Joint Strategic Needs Assessment North East Essex, 2013). Heart failure is a common life limiting condition affecting more than 10% of those over 75 years (Mosterd, Hoes, de Bruyne, Deckers et al ., 1999). Therefore the number of people living with heart failure in our community is likely to rise significantly. People with heart failure are under-represented on palliative care registers (Gadoud, Kane, Macleod, Ansell et al ., 2014). Only 4% of referrals to St Helena in 2016/17 were for people with heart failure. Aim: To begin to address the inequity of palliative care provision to local people living with advanced heart failure by: increasing referrals to the hospice for people with heart failure; improving access to the local electronic palliative care coordination system (EPaCCS); delivering a coordinated approach between community heart failure services and the hospice and improving knowledge of palliative care in heart failure across both services. Method: We allocated medical time to heart failure service coordination and created a day centre group specifically for people with heart failure. We created a heart failure link nurse role and hosted shared education events on heart failure and palliative care between the hospital, community and hospice services. We developed an inpatient diuresis protocol and audit and created a heart failure and advance care planning animation. Results: Referrals to the hospice increased from 86 to 142 per year, the number of people with heart disease on EPaCCs increased from 136 to 323 and the number of inpatient admissions for people with heart failure increased from 11 to 21. Conclusion: A collaborative focus on a population with a specific diagnosis can begin to address inequality in palliative care provision.